Roles of RAD51 and RTEL1 in telomere and rDNA stability in Physcomitrella patens - Goffová, Ivana; Vágnerová, Radka; Peška, Vratislav; Franek, Michal; Havlová, Kateřina; Holá, Marcela; Zachová, Dagmar; Fojtová, Miloslava; Cuming, Andrew; Kamisugi, Yasuko; Angelis, Karel J; Fajkus, Jiří (The Plant journal, 2019)
Telomeres and ribosomal RNA genes (rDNA) are essential for cell survival and particularly sensitive to factors affecting genome stability. Here, we examine the role of RAD51 and its antagonist, RTEL1, in the moss Physcomitrella patens. In corresponding mutants, we analyse their sensitivity to DNA damage, the maintenance of telomeres and rDNA, and repair of double-stranded breaks (DSBs) induced by genotoxins with various modes of action. While the loss of RTEL1 results in rapid telomere shortening, concurrent loss of both RAD51 genes has no effect on telomere lengths. We further demonstrate here the linked arrangement of 5S and 45S rRNA genes in P. patens. The spacer between 5S and 18S rRNA genes, especially the region downstream from the transcription start site, shows conspicuous clustering of sites with a high propensity to form quadruplex (G4) structures. Copy numbers of 5S and 18S rDNA are reduced moderately in the pprtel1 mutant, and significantly in the double pprad51-1-2 mutant, with no progression during subsequent cultivation. While reductions in 45S rDNA copy numbers observed in pprtel1 and pprad51-1-2 plants apply also to 5S rDNA, changes in transcript levels are different for 45S and 5S rRNA, indicating their independent transcription by RNA polymerase I and III, respectively. The loss of SOL (Sog One-Like), a transcription factor regulating numerous genes involved in DSB repair, increases the rate of DSB repair in dividing as well as differentiated tissue, and through deactivation of G2/M cell-cycle checkpoint allows the cell-cycle progression manifested as a phenotype resistant to bleomycin.
Keywords: Rad51 Recombinase; DNA Helicases; ribosomal RNA genes; RNA, Ribosomal, 5S; RNA ribozomální 18S; Bryopsida; DNA, Ribosomal; genome stability; telomere; telomery; Transcription Factors; genetické lokusy; RTEL1; rekombinasa Rad51; mutace; DNA-helikasy; RNA ribozomální 5S; nestabilita genomu; mechy; Physcomitrella patens; Telomere; RNA ribozomální; rostlinné proteiny; RNA, Ribosomal; Plant Proteins; ribozomální DNA; Genomic Instability; transkripční faktory; RNA, Ribosomal, 18S; Mutation; RAD51; Sog One-Like; Genetic Loci